Regional assessment of trash in Southern California coastal watersheds, United States - McLaughlin, Karen; Mazor, Raphael; Sutula, Martha; Schiff, Kenneth (Frontiers in Environmental Science, 2023)
Abstract Trash impairment of watersheds has been recognized as a worldwide environmental problem. Trash monitoring in streams and rivers is necessary to enhance our understanding of its effects on freshwater habitats and the role of streams as a conduit for transport to marine environments. Southern California, with a population of over 22 million, is home to nearly 7,400 kilometers of wadeable streams in watersheds spanning a variety of land uses, making it an ideal region to study the extent and magnitude of trash and trash types (plastic, metal, glass, etc.) and identify relationships between land use and amount of trash. These data can be used to develop mitigation strategies and evaluate management successes. We found that 77% of southern California’s coastal stream kilometers contained trash, with an estimated stock of 7 million pieces of trash. Of the types enumerated, plastic trash was the most ubiquitous, present in 69% of stream kilometers, and the most abundant, with an estimated stock of over 4.3 million pieces of plastic. The most common items were single-use plastic containers, wrappers, and plastic bags. Urban land use was associated with the greatest extent and magnitude of trash, with levels nearly double those found in open land uses. Trash was strongly associated with indicators of human activity and development in watersheds. Road density and proximity to roads and parking lots were strongly associated with increased trash in watersheds. This survey also suggested that management actions had a positive effect on trash count. Since the previous trash survey in southern California streams in 2011-2013, a statewide ban on plastic bags was implemented in 2016. We found a significant decrease in the number of bags within streams in the present survey compared to the previous survey.